Aula de arte na educação básica: um estudo sobre as concepções de professoras atuantes em escolas públicas na cidade de São Carlos-SP - Godoy, Karen Adriana (2020)
This work investigated the conceptions of Art teaching by teachers working in public schools in the city of São Carlos / SP. As specific objectives, it was intended: to explore which artistic languages the teachers consider to be valid for teaching Art; identify which activities they expect to be carried out in the teaching of Arts; understand why these teachers consider such activities to be valid for teaching Art; to verify the role of art teaching at school for these teachers; and to analyze their conceptions regarding Art teaching at school. We rely on authors who discuss topics such as: “What is Art”; “Legislation on teaching Art”; and “Function and conceptions about teaching Art”. This is a qualitative research, in which a study of interviews was carried out, and which used the semi-structured interview as a data collection technique. For data treatment, content analysis was performed. Four art teachers from the Municipal and State Education Networks were interviewed, in schools located in São Carlos / SP. The data allowed to conclude that the legislation referring to the teaching of Art in schools does not offer concrete subsidies for the teaching work in Art of teachers. In addition, it was possible to conclude that the demands in relation to professional training and teaching practice are still in great disagreement, causing the area to weaken, professional devaluation and an art teaching with little theoretical basis. We were also able to conclude that the interviewees consider the presence and teaching of the four artistic languages at school to be important, but when reporting on the activities carried out in Art classes, the vast majority rely on examples of the visual language or only in the area of their training.